A iniquidade do financiamento nas aquisições de medicamentos - gastos catastróficos e empobrecimento - Isabel Cristina Martins Santos (2015)
The Brazilian health system has a financing structure in which the direct disbursements of families have a majority portion. In health care, where much of the funding is for direct disbursement, this is considered iniquitativo as those in lower socioeconomic positions can have their reduced access because they lack sufficient resources. In Brazil, most of the drugs are by direct disbursement, an important component in the budget of the health of families. One has to consider that part of the access to these drugs is acquired without the need of disbursement, i.e. free of charge. This study aims to analyze the drug spending in the budget of families from the Family Budget Survey (POF) 2008-2009 and 2002-2003 emphasizing the non-monetary costs of medicines. Non-monetary costs are those that have been acquired without the need for monetary disbursement, i.e. by public or private donation. The prevalence of catastrophic expenditures (GC) and impoverishment of families stemming from drug expenditures were estimated. The construction of these two indicators is important because the incidence of GC and impoverishment are the consequences of significant funding for direct disbursement. . The data source was the Consumer Expenditure Survey 2008-2009 and from 2002 to 2003. The main conclusion is that the access of non-cash medicines and allow the medical treatment is carried out, reduces the budgetary impact checked both catastrophic spending as the family impoverishment. However, there is also found that further significant prevalence of certain groups in catastrophic costs and that they should therefore be more accesses by non-monetary form, thereby reducing its high expense for the purchase of drugs.